Organizational design redefined by design thinking. Case studies in the hotel industry - Lamelas, D.; Lamelas, J. P.; Filipe, J. (International Journal of Latest Trends in Finance and Economics Sciences, 2015)
This paper presents two different case studies, where the design thinking process, among other theories that came from classic design were used at the level of the organization design, organizational structure, process design and business design. Considering the exhaustive information brought from Classic Design Theory, a new philosophy was created for organizations based on that theory. Some frameworks were also created to help those who want to practise these technics and theories to design their own organization in a more profound, adequate and creative way. A study is made in the tourism sector based on two projects, one to be developed in the northern region of Portugal and the other one, already implemented, called “Biovilla Sustainability” located 40km away from Lisbon. The aim of this paper is to show how the identification and experimentation of concepts and methods used in classical design allow a better understanding of the implications they have in the engineering organization design theory and how their application may bring strong positive implications in terms of Simplicity (everyone understands); Functionality (it serves the purpose); Beauty (people love it); Sustainability (it must integrate time) and Viability of such projects, never forgetting the users and context where the project is embedded.